Atonement and the Death of Christ: An Exegetical, Historical, and Philosophical Exploration - Wagers, Brian Keith (Trinity journal, 2023)
Review of Craig, William Lane. Atonement and the Death of Christ: An Exegetical, Historical, and Philosophical Exploration. Publisher: Waco, TX : Baylor University Press, 2020. ISBN: 978-1-4813-1204-2.